The Choice of Sports Affects Mental Rotation Performance in Adolescents - Pietsch, Stefanie; Jansen, Petra; Lehmann, Jennifer (Frontiers in Neuroscience, 2019)
This study investigates mental rotation performance of adolescent female dancers and soccer players in object-based and egocentric mental rotation tasks using human body stimuli. 60 young females, 30 soccer players and 30 dancers (not twosome), completed a chronometric mental rotation task with object-based and egocentric transformation of male and female figures, which were displayed either in front or back view. During their sport-specific activity soccer-players and dancers very often have to adapt their movements to the movement of a partner or opponent, soccer-players especially in front view positions. While for soccer-players reaction time often is crucial for sporting success, dancers mainly focus on the accuracy of their movements. Therefore, we expect significantly faster reaction times for soccer players for front view stimuli but no differences between soccer players and dancers for back view stimuli. The main result was that soccer-players showed a significantly shorter reaction time than dancers for stimuli presented in front view in object based and egocentric transformation. There was no such difference, when the stimuli were presented in the back view. Contrary to literature we didn´t find significantly higher reaction times and error rates for stimuli presented in front view compared to back view in general but only for egocentric transformations. The results of this study show that specific sports effect individual aspects of mental rotation performance.